Private Laws of the Territory of Kansas 138 (1860) - (:unkn) unknown (My University, 1860)
An Act to Amend and Consolidate the Several Acts Relating to the City of Lawrence, § 35, pt. 19: Granted the city of Lawrence the authority to regulate the discharging of firearms, rockets, gunpowder, fireworks within the streets or vicinity of any building.
Keywords: DISCHARGE